A Semiotics Analysis of the Web Series ‘DARK’ [Season:1 (2017)] - Ganesh P, Nawin Shankar (Journal of Advanced Research in Journalism & Mass Communication, 2023)
The visual arts speak to everyone. Throughout history, artists have used their artwork and paintings to convey stories. Some of the tales are given exactly, whereas others have been illustrated with artwork on walls, fabrics, papers. The realm of art has seen a variety of alterations and transformations during this period. The meaning of web series work in narrative is frequently enhanced by the utilisation of other creative forms. This study will look into the significance of mis en scene in the usage of visual storytelling in web series. This research of semiotic analysis uses the German web series “DARK [season-1 (2017)]- by Baran odar and Jantje Friese’s” as a sample. The German web series DARK [season-1 (2017)] uses the qualitative methodology to analyse the signifier and signified representation semiotics. The science fiction elements employed in the German online series DARK (season 1, 2017) relate to occurrences in real life as well as the sociological and psychological context. The analysis’s findings demonstrated that Saussure’s semiotic theory could be used to interpret these signs’ meanings in the Mise en scene. The results of the semiotic analysis will enable us to comprehend the importance of Mise en scene in web series and how it is utilised in visual storytelling. How to cite this article: Ganesh PNS. A Semiotics Analysis of the Web Series ‘DARK’ [Season:1 (2017)]. J Adv Res Jrnl Mass Comm 2023; 10(1): 1-7. DOI: https://doi.org/10.24321/2395.3810.202301